Upaya Perbaikan Proses Produksi di PT. X - Natasha Nauli (Jurnal Titra, 2019)
PT. X is one of leading company in manufacturing that produces the packaging plastic equipment for cosmetics. The company has many problems that are the highest prices of raw material and the rising pay for the operators, which has an impact on the production cost. Therefore, the company want to reduce the production cost by analyzing the production process. The methods that are used in this research are line balancing, motion study and waste analysis. The result of analyzing stage showed there are five problems, they are unnecessary process, over processing waste, transportation waste, line balancing and motion study problem. Some improvements are made based on the analysis result. They are scheduling mold maintenance, calibrating censor machine, changing the amount of the product in one-way transportation, reallocating the operators and improving the motion of assembly operator. The result of the improvement that has been implemented is the increasing of production output from 7200 products to 7400 products.